Community Innovations Fund(CIF) for CSA - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
the concept is adopted as Village Development Fund(VDF) in the implementation of the Biodiversity Corridors Conservation Project in Cambodia; and being promoted to local governments in the Philippines; and was piloted in MyLoi Climate Smart Village in Vietnam